Exploration of the Link Between Nonverbal Communication, Affectivity, and Demographics - Abbas, Mariyam; Fatima, Mahvish (Psychology in the schools, 2025)
ABSTRACT Effective communication is vital in both social and professional contexts, yet the nuanced relationship between nonverbal communication (NVC) and affectivity, particularly in relation to demographic factors, has not been fully understood. The lack of clarity in how these elements interact poses a challenge in developing tailored communication strategies that resonate across diverse populations. To address this, the study investigates the connection between NVC and affectivity, focusing on gender, age, and education as key demographic factors. A sample of 200 participants (64.5% males, 35.5% females) was analyzed using a 26‐item Nonverbal Communication and Affectivity (NVCA) scale. The study found that males exhibited higher levels of both NVC and affectivity. Age significantly influenced NVC, but its effect on affectivity was not significant. Educational level did not significantly affect either NVC or affectivity. The study showed the importance of demographic considerations in communication practices and calls for further research to deepen our understanding of the interplay between NVC, affectivity, and socio‐cultural influences. Summary Nonverbal Communication Matters: Recognizing and understanding nonverbal cues are essential for effective communication in professional and social settings. Demographics Shape Communication: Gender, age, and educational background significantly influence NVC patterns. Practitioners should consider these demographic factors when interpreting and tailoring communication strategies for clients, students, colleagues, or customers. Leveraging NVC for Positive Outcomes: Insights from this study can guide practitioners in designing interventions to enhance nonverbal communication skills and foster positive affectivity, thereby improving well‐being and interpersonal relationships across diverse groups.